2011
DOI: 10.1107/s1744309111027424
|View full text |Cite
|
Sign up to set email alerts
|

Gene Composerin a structural genomics environment

Abstract: The structural genomics effort at the Seattle Structural Genomics Center for Infectious Disease (SSGCID) requires the manipulation of large numbers of amino-acid sequences and the underlying DNA sequences which are to be cloned into expression vectors. To improve efficiency in high-throughput protein structure determination, a database software package, Gene Composer, has been developed which facilitates the information-rich design of protein constructs and their underlying gene sequences. With its modular wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Multiple crystallization efforts with native sequence BpML1 constructs with tags removed failed to yield crystals. Therefore, to obtain alternative crystal forms not dependent on the cleavage site sequence interaction with the protein, a series of BpML1 point mutations was designed using GeneComposer software (31,32,52). Via GeneComposer, specific residues were identified that could alter the crystal lattice while minimizing the impact on binding site topology, based on crystal contacts observed in the apo form of the BpML1 structure.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple crystallization efforts with native sequence BpML1 constructs with tags removed failed to yield crystals. Therefore, to obtain alternative crystal forms not dependent on the cleavage site sequence interaction with the protein, a series of BpML1 point mutations was designed using GeneComposer software (31,32,52). Via GeneComposer, specific residues were identified that could alter the crystal lattice while minimizing the impact on binding site topology, based on crystal contacts observed in the apo form of the BpML1 structure.…”
Section: Resultsmentioning
confidence: 99%
“…Starting from the amino-acid sequences for these two PDF proteins, gene sequences were designed for expression in E. coli using Gene Composer (Emerald BioSystems, Bainbridge Island, WA, USA) (Lorimer et al , 2009; Lorimer et al , 2011). Back-translation of the amino-acid sequences employed a Universal Codon Usage Table designed to accommodate expression in E. coli with a minimum usage threshold of 2%.…”
Section: Methodsmentioning
confidence: 99%
“…Genes were designed for optimal expression in E. coli using Gene Composer (Emerald BioSystems, Bainbridge Island WA) [76] [77] . Amino acid sequences were back-translated using an E. coli codon usage table with a minimum usage cutoff of 2%.…”
Section: Methodsmentioning
confidence: 99%